Implementation of the Inquiring Minds Want to Know Strategy to Increase the Learning Spirit of Class IV Regular A Students in SKI Learning at TMI Al-Amien Prenduan - Gunawan Wibisono; Mohammad Firdaus (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This study aims to conceptually analyze the potential of the Inquiring Minds Want to Know (IMWTK) method in increasing learning enthusiasm in Islamic Cultural History (SKI) subjects. The research method used is qualitative library research with a literature search of the last 5 years (2021–2025) through journal articles, proceedings, and relevant scientific sources discussing IMWTK, inquiry-based learning, motivation/situational motivation, curiosity, and SKI learning. The literature data were analyzed through thematic analysis to produce: (1) a syntactic description of IMWTK and its learning principles, (2) a mapping of the IMWTK mechanism that stimulates curiosity, engagement, and self-regulation, which are the foundations of learning enthusiasm, and (3) an applicable IMWTK implementation design for the SKI material context. The results of the study show that IMWTK has the potential to increase enthusiasm for learning SKI because it begins the learning process with questions/riddles that arouse curiosity gaps, provides space for opinion and argument, and directs students to verify answers through source searches and meaningful discussions. In conclusion, IMWTK is worthy of being used as an alternative active-inquiry strategy in SKI learning, provided that there is support in the form of question design, availability of sources, and assessments that evaluate students' thinking processes and participation.